Expert Android programming : master skills to build enterprise grade Android applications - Mainkar, Prajyot (Packt Publishing, 2017)
Become a pro with the latest Android SDK and create state of the art applications for Android. About This Book Dive deep into Android development with practical hands on examples to help you in each stage. Develop smart professional grade apps for the latest Android N version and become a pro android developer. Unclog your development highway by utilising the industry standard best practices techniques. Who This Book Is For This book is for mobile developers having some expertise in building android apps and who wish to now take a leap into building complex app such as Zomato, using latest Android N power of Google. What You Will Learn Building UI/UX following best industry practices Development of Zomato Clone Measure and improve app performance Improving app using test mechanisms Bringing the app live on the play store In Detail Android O brings a number of important changes for the users as well as the developers. If you want to create smart android applications which are fast, lightweight and also highly efficient then this is the book that will solve all your problems. You will create a complex enterprise grade app in this book. You will get a quick refresher of the latest android SDK and how to configure your development environment. Then you will move onto creating app layouts, component and module building, creating smart and efficient UIs. The most important part of a modern day app is how real time they are. With this book, you will create a smooth back-end for your app, ensure dynamic and real time communication between different app layers. As we move on, you will learn to leverage the different Android APIs and create an efficient SQLite data layer for your apps. You will implement effective testing techniques to make your app reliable and robust and finally you will learn to deploy it efficiently. The multiple stages of android development will also be simplified by giving you an industry standard set of best practices. Style and approach This book will have a dedicated practical tutorial style approach with focus on professional & enterprise grade android app development. The examples in each chapter will be modular and will also help you to create a complete fully fueatured android app by the end of the book.